2015
DOI: 10.1074/mcp.o114.047035
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Centric Proteome Analysis: An Alternative Strategy for the Analysis of Tandem Mass Spectrometry Data

Abstract: In mass spectrometry-based bottom-up proteomics, data-independent acquisition is an emerging technique because of its comprehensive and unbiased sampling of precursor ions. However, current data-independent acquisition methods use wide precursor isolation windows, resulting in cofragmentation and complex mixture spectra. Thus, conventional database searching tools that identify peptides by interpreting individual tandem MS spectra are inherently limited in analyzing data-independent acquisition data. Here we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
176
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 56 publications
0
176
0
Order By: Relevance
“…For example, Ting et al presented a perspective on spectrum-centric analysis versus peptide-centric analysis, the latter of which assesses the probability that a peptide is present without requiring a spectral library [47]. This ‘peptide-centric analysis’ has been implemented in the software PECAN, which tests directly for statistical probability that the query peptides are present [47]. Another tool recently introduced by our group makes use of uDIA and isotopic labeling to assess absolute stoichiometry of lysine acetylation and succinylation [53].…”
Section: Bioinformatic Resources For Analysis Of Data From Udiamentioning
confidence: 99%
“…For example, Ting et al presented a perspective on spectrum-centric analysis versus peptide-centric analysis, the latter of which assesses the probability that a peptide is present without requiring a spectral library [47]. This ‘peptide-centric analysis’ has been implemented in the software PECAN, which tests directly for statistical probability that the query peptides are present [47]. Another tool recently introduced by our group makes use of uDIA and isotopic labeling to assess absolute stoichiometry of lysine acetylation and succinylation [53].…”
Section: Bioinformatic Resources For Analysis Of Data From Udiamentioning
confidence: 99%
“…Data‐independent acquisition (DIA) such as Sequential Window Acquisition of all Theoretical Fragment ion spectra (SWATH) forgo pre‐programmed precursor‐fragment pairs, widening the isolation windows to activate all ions in a pre‐specified mass‐to‐charge (m/z) range. A detailed review of DIA methodology can be found elsewhere, including peptide‐centric approaches to DIA . It is also possible, through MS1 filtering informatics techniques, to use data dependent acquisition (DDA) for quantitative analysis as opposed to conventional detection analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, methods for quantitative comparisons of site-specific protein glycoforms have only begun to emerge (9). While the comparative analysis of proteins by data independent acquisition (DIA) has improved the efficiency of quantitative proteomics analyses (20;21), applications of DIA methods to the analysis of posttranslational modifications are limited and virtually non-existent for glycoproteins (22). In this paper, we introduce a workflow for DIA analysis of N-glycopeptides under soft CID fragmentation conditions and document applicability of the glycopeptide DIA (Glycopeptide SWATH or GP-SWATH) workflow to the comparative analysis of fucosylated complex glycoforms of ten abundant plasma glycoprotein groups in the context of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%